A V-LINC Analysis of Northern Ireland's Cyber Security Ecosystem. (2020) - (College teacher), Hobbs, John; Byrne, Eoin; Sargent, Cliodhna; Kuli, Tabona; Cork Institute of Technology., V-LINC Research Group,; Northern Ireland Cyber Security Cluster (Organization),
No abstract available